Effect of strontium addition on ferroelectric phase transition of PZT thin films prepared by chemical route - Pontes, Fenelon Martinho Lima [UNESP]; Galhiane, Mario Sergio [UNESP]; Santos, L. S. [UNESP]; Gavino, A. [UNESP]; Petit, L. A. [UNESP]; Pontes, D. S. L. [UNESP]; Longo, Elson [UNESP]; Chiquito, A. J.; Costa, C. E. F. (Springer, 2009)
The dependence of ferroelectric phase transition temperature as a function of strontium substitution in lead titanate zirconate thin films (referred here as PSZT) on platinum-coated silicon substrates was investigated. The dielectric study reveals that the material undergoes a diffuse type ferroelectric phase transition that depends on the substitution of Sr for Pb in PZT. At 100 kHz, the phase transition temperatures were 633, 613 and 516 K for PSZT10, PSZT20 and PSZT30 thin films, respectively. on the other hand, the results showed that the dependence of the dielectric constant upon the frequency does not reveal any relaxor behavior. The diffusivity increases with increasing Sr contents in the studied composition range. The experimental data obtained from measurements of the dielectric constant as a function of temperature and frequencies showed a classical behavior of ferroelectric phase transition in PSZT thin films, rather than a relaxor ferroelectric phase transition. The transition temperature decreases with increasing Sr contents due to the decrease in grain size, lattice decrease and local structural disorder.